Harnessing CXCR4 antagonists in stem cell mobilization, HIV infection, ischemic diseases, and oncology. Issue 4 (2nd August 2017) - Tsou, Lun Kelvin; Huang, Ying‐Huey; Song, Jen‐Shin; Ke, Yi‐Yu; Huang, Jing‐Kai; Shia, Kak‐Shan
Abstract: CXCR4 antagonists (e.g., Plerixafor TM ) have been successfully validated as stem cell mobilizers for peripheral blood stem cell transplantation. Applications of the CXCR4 antagonists have heralded the era of cell‐based therapy and opened a potential therapeutic horizon for many unmet medical needs such as kidney injury, ischemic stroke, cancer, and myocardial infarction. In this review, we first introduce the central role of CXCR4 in diverse cellular signaling pathways and discuss its involvement in several disease progressions. We then highlight the molecular design and optimization strategies for targeting CXCR4 from a large number of case studies, concluding that polyamines are the preferred CXCR4‐binding ligands compared to other structural options, presumably by mimicking the highly positively charged natural ligand CXCL12. These results could be further justified with computer‐aided docking into the CXCR4 crystal structure wherein both major and minor subpockets of the binding cavity are considered functionally important. Finally, from the clinical point of view, CXCR4 antagonists could mobilize hematopoietic stem/progenitor cells with long‐term repopulating capacity to the peripheral blood, promising to replace surgically obtained bone marrow cells as a preferred source for stem cell transplantation.